Order of Creation of Joint-Stock Companies in Turkestan In The Late Xix - Early Xx Centuries And Participation Of Foreign Capital In It - Otabek, Nasirov; Farhod, Usmanov; Javlonbek, Begaliyev (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the emergence, formation and development of capitalist production relations in the 17th century in Europe, the formation of the first joint-stock companies. In the second half of the 17th century, joint stock companies and trading companies began to appear in the Russian Empire. According to the field of activity, joint-stock companies in Russia were divided into 3 types: 1) trading organizations - shipbuilding, water supply and electricity supply, as well as various trade associations; 2) Production organizations - wool production, cotton production, dyeing and packaging, paper production, silk, leather goods and livestock products, engineering, oil and coal industries, lime production, chemical products, cotton picking, sugar, food, drinking water, tobacco products, etc.; 3) Credit institutions - commercial and land banks, a land loan, urban community, rural community banks, etc. The article analyzes the profit, management, production and export of goods in Turkestan.